The Analysis of Sentence Construction and Meaning Interpretation of English Break Verbs and their Verbs Equivalence in Buginese Language - Herlina herlina; Hamzah A Machmoed; Sukmawaty (EDUVELOP, 2022)
The purpose of this research is to compare the sentence form and meaning interpretation of 'Break' Verbs in English and Buginese. The sentence construction and the meaning interpretation of verbs confined to Break Verb from English and Buginese language were compared with regards to Dixon’s Affect Verbs Construction and Halliday’s Functional Grammar Construction. The data of this research were collected from two sources. The English data were collected from British National Corpus (BNC) while the Buginese Data was collected from field observation and interview on Soppeng Buginese speaking community. The data were collected and analyzed using Descriptive Qualitative Methods. According to the findings of this study, it was found eighteen Break Verbs in the English language and nineteen in the Buginese language; 2) The ‘Break’ Verbs in both languages are realized into sentences through a number of selections of constructions set up in the two theories that were examined in this research and some additional constructions where each construction plays some contribution to the meaning interpretation; 3) The Break Verbs found in both languages have some similarities and differences regarding their sentence construction and meaning interpretation.